Rutin Nanocrystals with Enhanced Anti-Inflammatory Activity: Preparation and Ex Vivo/In Vivo Evaluation in an Inflammatory Rat Model - Abeer S. Hassan; Ghareb M. Soliman (MDPI AG, 2022)
Rutin is a polyphenolic flavonoid with an interestingly wide therapeutic spectrum. However, its clinical benefits are limited by its poor aqueous solubility and low bioavailability. In an attempt to overcome these limitations, rutin nanocrystals were prepared using various stabilizers including nonionic surfactants and nonionic polymers. The nanocrystals were evaluated for particle size, zeta potential, drug entrapment efficiency, morphology, colloidal stability, rutin photostability, dissolution rate, and saturation solubility. The selected nanocrystal formulation was dispersed in a hydrogel base and the drug release kinetics and permeability through mouse skin were characterized. Rutin's anti-inflammatory efficacy was studied in a carrageenan-induced rat paw edema model. The nanocrystals had a size in the range of around 270-500 nm and a polydispersity index of around 0.3-0.5. Nanocrystals stabilized by hydroxypropyl beta-cyclodextrin (HP-β-CD) had the smallest particle size, highest drug entrapment efficiency, best colloidal stability, and highest drug photostability. Nanocrystals had around a 102- to 202-fold and 2.3- to 6.7-fold increase in the drug aqueous solubility and dissolution rate, respectively, depending on the type of stabilizer. HP-β-CD nanocrystals hydrogel had a significantly higher percent of drug released and permeated through the mouse skin compared with the free drug hydrogel. The cumulative drug amount permeated through the skin was 2.5-fold higher than that of the free drug hydrogel. In vivo studies showed that HP-β-CD-stabilized rutin nanocrystals hydrogel had significantly higher edema inhibition compared with the free drug hydrogel and commercial diclofenac sodium gel. These results highlight the potential of HP-β-CD-stabilized nanocrystals as a promising approach to enhance drug solubility, dissolution rate, and anti-inflammatory properties.